Effects of Assessment-recommendation-follow-up Protocol on the Employment of Individuals with Mental Retardation - Xiaohu CHEN; Shangkun WU; Yanwen XU (康复学报)
Objective:The purpose of the study is to investigate the effects of Assessment-recommendation-follow-up program on the employment of a cohort of individuals with mental retardation.Methods:A total of 139 individuals with mental retardation were recruited and participated vocational assessment with valpar component work sample (VCWS) in a rehabilitation center. Recommendation of attending job interview was provided according to assessment results, then a follow-up after three months was conducted to collect employment status.Results:Of the 139 participants, 67 participants were recommended to attend job interview in line with the assessment results. Eventually, 19 (28.36%) participants were successfully employed. A total of 15 participants with their test results matching MEETS or MEETS MAY EXCEED were all successfully employed. The job analysis results revealed that the current job position is matching with the job analysis in vocational assessment.Conclusion:People with mental retardation is recommended to receive specific pre-employment vocational assessment services, and the assessment results may help guide the employment process and increase the employment rate, eventually.